Redução da população de Caryocar brasiliense Camb na APA Pandeiros - Patricia Doerl Barroso (2021)
Caryocar brasiliense Camb is a native species of Brazilian Savanna, considered of extreme socioeconomic importance for extractivists, being a source of income and food. Areas of cerrado of northern Minas Geraishave shown a reduction in the population of C. brasiliense due to tree mortality. The objective of this study is to identify the factors responsible for the mortality and reduction of the population of C. brasiliense, in APA Pandeiros, Bonito de Minas; and test methodology for surveying tip drought and mortality of C. brasiliense in natural areas and validating the use of UAVs as a tool to monitor and estimate losses in the field. All of this, to subsidize the management and conservation of the species. In the first study, a field diagnosis was carried out, evaluating the tip drought occurrence and tree mortality, the occurrence of biotic diseases and pests, and the influence of abiotic factors in a sample area of 80 hectares with 199 individuals of C. brasiliense. The severity of the dryness, incidence of leaf spots and pequi tree borers were determined. Trees were measured to characterize the population. Laboratory analyzes were also carried out to identify biotic factors from plants with symptoms, isolating microorganisms, identifying and testing their pathogenicity. In the second study, a UAV PHANTOM 3 SE was used, equipped with a Sensor Pixels camera to collect images of the studied area, and the process was executed using the VARI (Visible Atmospherically Resistant Index) to obtain the severity index of the trees through the aerial images. Results of the first study showed that there is no isolated factor that causes the mortality of the C. brasiliense, the presence of borers and spots is not correlated with the symptom of tip drought. The fungus Lasiodiplodia theobromae was identified in materials with symptoms of dryness in the field and its pathogenicity was proven in the pequi tree. Leaf spots were detected caused by Colletotichum acutatum and the identified borer is a lepidoptera of the Cossidae family. The mortality rate increased in the years of assessment. In the second study, it was possible to validate the use of UAV for generating images that show the damage caused by tip drought in C. brasiliense, and the use of VARI to identify the different levels of severity found in the field. The research results validate a new methodology for monitoring and quantifying the mortality of C. brasiliense in the field and provide important information to support the management of the species, in a sustainable way and for its conservation.